Pendekatan Deep Learning pada Pembelajaran di Sekolah Dasar Gekbrong 1 Cianjur: Penelitian - Enjang Warman; Sajidin; Rachmat Setiawan; Arie Gifary; Waska Warta; Agus Mulyanto; Hanafiah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
To face the challenges of the current digital era, elementary school students must master two basic skills: literacy and numeracy. However, in practice, learning activities in schools are not effective in developing in-depth understanding. One approach that can be applied to achieve a deeper and more sustainable understanding of concepts is deep learning. This study aims to determine the application of the deep learning approach in literacy and numeracy learning in elementary schools. This study used a literature review method, which was carried out by searching, selecting, and critically analyzing literature from relevant journals, books, and research reports. The selection of sources took into account the credibility of the authors, the appropriateness of the theme, and publications within the last five years. Data analysis was conducted using thematic techniques to identify patterns and conceptual relationships between deep learning and literacy and numeracy learning. The results showed that the deep learning approach improves students' critical thinking skills, problem-solving skills, and conceptual understanding. This research is expected to further enhance teachers' insight in designing more effective learning strategies.